Analisis Air Bersih dan Sanitasi Lingkungan di Pelabuhan Penyebrangan Ulee Lheue Kota Banda Aceh Tahun 2025 - Irgi Sifa Multazam; Radhiah Zakaria; Dedi Andria (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Ulee Lheue Port is a major port in Banda Aceh with high human activity, potentially posing environmental health risks if clean water quality and sanitation are not properly managed. The port serves not only as a transit point but also as a public space with intensive interaction between workers and service users. This study aims to assess clean water quality based on physical and chemical parameters, water availability, environmental conditions, and the sanitation adequacy of public facilities. This study used an observational method with a descriptive design. Data collection was conducted through direct observation, water quality measurements, and environmental sanitation and hygiene assessments. Samples were taken at several strategic points: the right lobby restroom, the left lobby restroom, the canteen restroom, and the prayer room. Parameters analyzed included physical aspects (odor, taste, color, turbidity), chemical aspects (pH), clean water availability, fly density, and the sanitation adequacy of public facilities. The results showed that the physical and chemical quality of the water generally met quality standards, with turbidity ranging from 0.10 to 0.55 NTU and a pH of 7, well within the standard range of 6.5 to 8.5. However, all samples did not meet taste standards, as they were identified as bitter and sweet. Clean water availability reached 100%, sourced from drilled wells. The highest fly densities were found in canteens and polling stations (TPS). It was concluded that water quality was relatively good, but sanitation in public facilities remained at risk, necessitating continuous improvement in vector management and control.